2011
DOI: 10.1088/0022-3727/44/30/305302
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behaviour of carbon monoxide at the photostimulated surface of ZnO nanowires

Abstract: Dear Editor of the Journal of Physics D: Applied Physics:We are very thankful for the advises from the reviewers and the editor. The manuscript (Article ID: D/393066/PAP) has already been revised according to the comments (resubmitted online).Following are the comments and the answers, corresponding the second referee's report: "I find the paper to be well written,…, I recommend this paper for publication." We appreciate your taking time to review the manuscript and your commendation.corresponding the third re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(51 reference statements)
0
2
1
Order By: Relevance
“…A similar result was observed by Wang, who used vertically aligned ZnO nanowires for CO sensing with light illumination at low intensity. Different from other CO sensing results where CO acts as the reducing gas, here CO caused the resistance of ZnO to increase more after removing the LED source, which indicated that CO worked as an oxidizing gas that trapped electrons from ZnO [ 53 ]. In conclusion, it is believed that the reported results confirm that there is no absolute measure on whether an analyte is reductive or oxidative, it is a question of how the energy levels of the analyte are relative to the sensing material.…”
Section: Pure Metal Oxide Materials For Gas Sensingcontrasting
confidence: 64%
“…A similar result was observed by Wang, who used vertically aligned ZnO nanowires for CO sensing with light illumination at low intensity. Different from other CO sensing results where CO acts as the reducing gas, here CO caused the resistance of ZnO to increase more after removing the LED source, which indicated that CO worked as an oxidizing gas that trapped electrons from ZnO [ 53 ]. In conclusion, it is believed that the reported results confirm that there is no absolute measure on whether an analyte is reductive or oxidative, it is a question of how the energy levels of the analyte are relative to the sensing material.…”
Section: Pure Metal Oxide Materials For Gas Sensingcontrasting
confidence: 64%
“…The response to all other interfering coexisting residual gases in the detecting system (such as H 2 O or O 2 , which is below 1 ppm) is marginal and can be excluded. 27 In the present work, the oxidizing behavior of CO was additionally investigated using XPS studies. For this, a fresh sample with dense NWs was scanned at each step of UV pretreatment and CO exposure and subsequently compared to the as-grown NWs.…”
Section: Pl Measurement Of Zno Nws At Rt As Shown Inmentioning
confidence: 99%
“…When explaining the mechanism of sensor properties, some authors consider the direct interaction of chemisorbed molecules of organic substances with photoexcited charge carriers, similar to photocatalytic reactions [ 49 , 185 , 186 , 187 ]. For example, in work [ 49 ], oxidation of ethanol vapors on the ZnO surface under UV irradiation is described by the following processes (Equations (21)–(23)): …”
Section: Mechanisms Of Light Activated Gas Sensingmentioning
confidence: 99%